Behavioral impairments following repeated intranasal glyphosate-based herbicide administration in mice - Baier, Carlos Javier (2017)
Inhalation or intranasal (IN) administration of neurotoxicants could constitute a route of toxin delivery to the brain. Pesticides have been proposed as the main environmental factor associated with the etiology of neurodegenerative disorders. In Argentina, the area used for glyphosate (Gly)-resistant crops are sprayed annually with ~ 200 million liters of Gly-based herbicides (Gly-BHs). Gly residues are often found in the environment, and considering the frequency and amount of its applications, it is probable that the inhalation of Gly-BHs occurs. The present study investigates the neurobehavioral effects of repeated IN administration of Gly-BH in male CF-1 mice (~ 2 mg/nostrils/day) three days a week, during four weeks (50 mg/kg/day). Locomotor activity and anxiety levels were studied by the Open Field (OF) test. Anxiety was also analyzed through the plus maze (PM) test. Novel Object Recognition (NOR) test was used for recognition memory analysis. Repeated IN Gly-BH administration in mice decreased the ambulatory activity. Moreover, Gly-BH treated mice showed a pronounced increase in thigmotaxis, compared to control group, indicating higher anxiety levels. The anxiogenic behavior in Gly-BH treated mice was then confirmed by PM test. The recognition memory was significantly impaired after 6 h in the Gly-BH treated group. No differences were observed between both groups when the NOR test was performed 24 h after. The present study reveals that repeated IN exposure to Gly-BH in mice affects the central nervous system probably altering neurotransmission pathways that participate or regulate locomotor activity, anxiety and memory.